An assessment of high overall pressure ratio intercooled engines for civil aviation - Camilleri, William (Cranfield University, 2014)
As gas turbine technology matures, further significant improvements in engine efficiency will be difficult to achieve without the implementation of new aero-engine configurations. This thesis delivers an original contribution to knowledge by comparing the design, performance, fuel burn and emission characteristics of a novel geared intercooled reversed flow core concept with those of a conventional geared intercooled straight flow core concept. This thesis also outlines a novel methodology for the characterisation of uncertainty at the conceptual design phase which is useful for the comparison of competing concepts. Conventional intercooled aero-engine concepts suffer from high over-tip leakage losses in the high pressure compressor, high pressure losses in the intercooler installation and increased weight and drag whereas the geared intercooled reversed flow core concept overcomes some of these limitations. The HP-spool configuration of the reversed core concept allows for an increase in blade height, a reduction in over-tip leakage losses and an increase in overall pressure ratio. It was concluded that a 1-pass intercooler would be the lightest and most compact design while a 2-pass intercooler would be easier to manufacture. In the reversed flow core concept the increased length of the 2-pass intercooler could be accommodated. In this concept the mixer also allows for a reduction in fan pressure ratio and a useful reduction in component losses. Both intercooled concepts were shown to benefit from the use of a variable area bypass nozzle for the reduction of take-off combustor outlet temperature and cruise specific fuel consumption. The intercooled cycles were optimised for minimum fuel burn and it was found that the reversed flow core concept benefits from higher overall pressure ratio and lower fan pressure ratio for an equivalent specific thrust. This leads to an improvement in thermal efficiency and more than a 1.6% improvement in block fuel burn. The NOx during landing and take-off as well as during cruise was found to be slightly more severe for the reversed flow core concept due to its higher overall pressure ratio. The contrails emissions of this concept were occasionally higher than for a year 2000 turbofan but only slightly higher than for the straight core concept. This dissertation shows that in spite of input uncertainty the reversed flow core intercooled engine is a promising concept. Further research should focus on higher fidelity structural and aerodynamic modelling.